(untitled) (Bangladesh Journal of Botany, 2019)
Composition of free amino acid in waxy maize DH lines was analysed and the nutritional quality of waxy maize germplasm resources was evaluated by o-phthaladehyde (OPA) pre-column derivatization reversed-phase high performance liquid chromatography (HPLC). Results obtained showed that there were at least 14 kinds of free amino acids, DH57 line had the highest (25.185 mg/g), and DH21 line had the lowest (6.203 mg/g) and the average was 12.226 mg/g. The contents of essential amino acids varied from 2.59 to 14.09 mg/g, accounting for 29.55 - 75.64% of the total free amino acids. The quality of free amino acids was evaluated by comprehensive indices with principal component analysis and the first top three DH lines were DH57, DH59 and DH55. The contents of free amino acids in 60 waxy maize DH lines had obvious genetic diversity. As to the free amino acid content, the amino acids quality of DH57, DH59 and DH55 were the best, while DH21 was the worst. Results provide a theoretical guidance for the cultivation of new varieties of waxy maize with good quality.